The m6A RNA Modification Modulates Gene Expression and Fibrosis-Related Pathways in Hypertrophic Scar - Liu, Si-Yu; Wu, Jun-Jie; Chen, Zhong-hua; Zou, Ming-Li; Teng, Ying-ying; Zhang, Kai-Wen; Li, Yue-Yue; Guo, Dang-yang; Yuan, Feng-Lai (Frontiers in Cell and Developmental Biology, 2021)
Purpose: To systematically analyze the overall m6A modification pattern in hyperplastic scars (HS). Methods: The m6A modification patterns in HS and normal skin (NS) tissues were described by m6A sequencing and RNA sequencing, and subsequently bioinformatics analysis was performed. The m6A-related RNA was immunoprecipitated and verified by real-time quantitative PCR. Results: The appearance of 14,791 new m6A peaks in the HS sample was accompanied by the disappearance of 7,835 peaks. The unique m6A-related genes in HS were thus associated with fibrosis-related pathways. We identified the differentially expressed mRNA transcripts in HS samples with hyper-methylated or hypo-methylated m6A peaks. Conclusion: This study is the first to map the m6A transcriptome of human HS, which may help clarify the possible mechanism of m6A-mediated gene expression regulation.